2014
DOI: 10.1093/ntr/ntu139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Income on Demand for Potentially Real Cigarettes

Abstract: IntroductionEconomic demand analyses quantify the relationship between the cost of a commodity and population-level measures of consumption of that commodity. In the case of cigarettes, these analyses largely depend on abrupt fluctuations in price caused by the assessment of new taxes on cigarettes. Studies of this type have found that cigarette consumption is related to price, and that the sensitivity to price, or demand elasticity, is greatest among lower income people.1-3 Behavioral economic demand analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…Thus, in both experiments when the prices of conventional cigarettes increased resulting in decreased consumption, participants compensated with nonstudy combustible tobacco products (mostly cigarettes), consistent with a previous report, 14 and (3) the presence or absence of cigarillos in the ETM is related to purchasing of nonstudy provided cigarettes. Significant differences between the slopes indicate that when cigarillos were available in the ETM, participants were less likely to break study protocol by purchasing outside products, likely a result of high levels of substitution with cigarillos in Experiment 1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, in both experiments when the prices of conventional cigarettes increased resulting in decreased consumption, participants compensated with nonstudy combustible tobacco products (mostly cigarettes), consistent with a previous report, 14 and (3) the presence or absence of cigarillos in the ETM is related to purchasing of nonstudy provided cigarettes. Significant differences between the slopes indicate that when cigarillos were available in the ETM, participants were less likely to break study protocol by purchasing outside products, likely a result of high levels of substitution with cigarillos in Experiment 1.…”
Section: Discussionsupporting
confidence: 88%
“…[21][22][23] More recently, participants purchased conventional cigarettes at various prices in the laboratory for use in their daily life permitting interactions with real world circumstances. 14,20 The ETM is the next step in the evolution of this methodology to study reinforcer demand and substitution in an ever more naturalistic context. Where the evolution of this method may lead is beyond the scope of this article, but may be important for the future study of the behavioral economics of tobacco product consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that simply asking participants to comply with the study rules is not sufficient for compliance and may be associated with particular actualized conditions. Only in an actual closed economy situation, can the opportunity for outside consumption be avoided (Koffarnus et al, 2015). Finally, these data may be biased toward e-cigarette substitution given the recent prior e-cigarette use required for inclusion in the study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study had shown that subjects given this study income expressed purchasing behavior that was comparable to self-reported nicotine consumption. 26 The five purchasing sessions were split into real (four sessions) and potentially real (one session) conditions, the order of these two conditions was counterbalanced across subjects. During each real session, the participants purchased and receive cigarettes at a single price, either $0.12, $0.25, $0.50, or $1.00 (presented in a randomized order).…”
Section: Methodsmentioning
confidence: 99%